(untitled) (Sirte Journal of Medical Sciences, 2023)
Coronary heart disease (CHD) is a leading cause of morbidity and mortality worldwide. Acute Myocardial Infarction (AMI) is the most common form of CHD and is responsible for over 15% of mortality every year. Hypertension (HTN) and diabetes mellitus (DM) are thought to be the most significant risk factors for developing CHD. Old age is a risk factor in both genders. However, Younger female are less likely to be affected compared to males. This study aims to assess the prevalence of HTN, DM, or both amongst patients admitted with acute MI (AMI) and to demonstrate the distribution of AMI according to age group and gender. Comorbidity data from 36 patients (22 males and 14 females) admitted with AMI to Ibn-Sina hospital between January 2018 and December 2018 was analyzed, tabulated, and graphed using Microsoft Excel.Our results showed that 8 patients (22.2%) had HTN prior to admission and 6 patients (16.6%) had DM, whilst 16 patients (44.4%) had both HTN and DM. 6 patients (16.6%) had neither HTN or DM. Male patients had the highest incidence of AMIs (22 patients, 62.5%). Furthermore, the highest incidence of AMIs in male patients were in the ‘40-59’ age group, as compared with the female group with the highest incidence of AMIs being in the ‘60-69’ age group. A combined co-morbidity of HTN and DM was shown to be a high-risk factor for the incidence of MI. Furthermore, MI incidence was shown to be higher in the male population, and presents at a younger age in males than females.